International Justice in the time of ‘outsourced illiberalism': Africa and the International Criminal Court - Mwenda Kailemia (Journal of Global Faultlines, 2016)
The purposes of this paper are, first, to demonstrate the inconsistencies of the international criminal justice practice, with a specific focus on the International Criminal Court' s (ICC) relationship with Africa, and, secondly, to demonstrate how such inconsistency is itself consistent- precisely because it flows in the direction of post-cold war neo-liberal ‘exceptionalism’. To explore the consistency of this inconsistency we deploy the notions of ‘McGuffins’ (the empty pretext which sets the narrative in motion but has no other value to the plot) popularised by Hitchcock' s films, and ‘The Invisible Gorilla’ (the optical illusion from a focus on an object under pressure) popularised by Chambris and Simons’ (2010) psychological experiment.